The Health Status of Labor Force in East Kalimantan Province: Effect of Individual Characteristics and Household Conditions - Heizer, Jaka Eben (Jurnal Ekonomi Kesehatan Indonesia, 2021)
The aims of this research are first, to explore the factors that are associated with health status. Second, to address the individual characteristics and household conditions that affect the health status of labor force, taking into account the urban-rural differences. This research utilized data from SUSENAS Cor 2018, and employed a cross sectional - multinomial logistic regression analysis method. The dependent variable is the health conditions of the labor force. The findings show that, age and number of household members were significant for both sick and very sick health status in all two type of areas analyzed. In urban and rural areas simultaneously gender, expenditure per capita, and drinking water were only significant for sick health group while marital status, education, employment status, sanitation, house area was only significant for very sick health status group. In urban areas, the results indicated that gender, employment status, and drinking water were only significant for sick health status, while marital status, education, sanitation, and house area significant for very sick health status. Moreover, in rural areas, marital status was only significant for sick health status whereas, sanitation and house area were significant for the very sick health status.